(untitled) - Gurr, M. I. (Mass., 2002)
Contents include abbreviations and definitions used in the study of lipids, routine analytical methods, fatty acid structure and metabolism, dietary lipids and lipids as energy stores, lipid transport, lipids in cellular structures and the metabolism of structural lipids. The book provides a most comprehensive treatment of the subject, making it essential reading for all those working with or studying lipids.
Keywords: Lipids